2022
DOI: 10.1590/s1678-9946202264002
|View full text |Cite
|
Sign up to set email alerts
|

Spurious infection by Calodium hepaticum (Bancroft, 1983) Moravec, 1982 and intestinal parasites in forest reserve dwellers in Western Brazilian Amazon

Abstract: Subsistence hunting is the main source of protein for forest reserve dwellers, contributing to the development of spurious infections by Calodium hepaticum, frequently associated with the consumption of the liver from wild mammals. The prevalence of infections by soil-transmitted helminths (STHs) and intestinal protozoa is considered an indicator of the social vulnerability of a country, besides providing information on habits, customs and quality of life of a given population. Intestinal parasites mostly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…R. nana eggs were also found in studies involving the feces of wild carnivores (wolves and foxes), and the authors suggested that the finding may have been due to the ingestion of infected rodents or even eggs laid in the environment by definitive hosts (Elmore et al, 2013;van Kesteren et al, 2015). Oliveira et al (2022) demonstrated humans being act as carriers of capillarid eggs (spurious infection) in the same locations in the Amazon region analyzed here. Likewise, the capillarid eggs reported may have been ingested through the consumption of the viscera of parasitized predated/hunted rodents, as Neves et al (2017) report dogs from the same areas in the state of Acre being fed with this type of material.…”
Section: Coproparasitological Examination Of Domestic Dogssupporting
confidence: 63%
“…R. nana eggs were also found in studies involving the feces of wild carnivores (wolves and foxes), and the authors suggested that the finding may have been due to the ingestion of infected rodents or even eggs laid in the environment by definitive hosts (Elmore et al, 2013;van Kesteren et al, 2015). Oliveira et al (2022) demonstrated humans being act as carriers of capillarid eggs (spurious infection) in the same locations in the Amazon region analyzed here. Likewise, the capillarid eggs reported may have been ingested through the consumption of the viscera of parasitized predated/hunted rodents, as Neves et al (2017) report dogs from the same areas in the state of Acre being fed with this type of material.…”
Section: Coproparasitological Examination Of Domestic Dogssupporting
confidence: 63%